2008
DOI: 10.1182/blood-2007-07-102798
|View full text |Cite
|
Sign up to set email alerts
|

Acute promyelocytic leukemia: from highly fatal to highly curable

Abstract: Acute promyelocytic leukemia (APL) is a distinct subtype of acute myeloid leukemia. Morphologically, it is identified as the M3 subtype of acute myeloid leukemia by the French-American-British classification and cytogenetically is characterized by a balanced reciprocal translocation between chromosomes 15 and 17, which results in the fusion between promyelocytic leukemia (PML) gene and retinoic acid receptor ␣ (RAR␣). It seems that the disease is the most malignant form of acute leukemia with a severe bleeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
916
1
25

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,143 publications
(953 citation statements)
references
References 94 publications
11
916
1
25
Order By: Relevance
“…Increased bone marrow FDG uptake at PET/CT is not a sufficient proof of bone marrow involvement in diffuse large B-cell lymphoma Consequently, they suggest that BMB can be omitted in case of unequivocal bone marrow involvement at FDG-PET/CT. Although the results of the study by Chen-Liang et al [1] underline the results of our previous study [2] that FDG-PET has a suboptimal sensitivity for the identification of bone marrow involvement in DLBCL, we cannot agree with their conclusion that bone marrow abnormalities at FDG-PET/CT can confidently designate advanced-stage disease. Increased focal FDG uptake in the marrow is not sufficient evidence to confirm bone marrow involvement.…”
Section: Author Contributionscontrasting
confidence: 69%
See 2 more Smart Citations
“…Increased bone marrow FDG uptake at PET/CT is not a sufficient proof of bone marrow involvement in diffuse large B-cell lymphoma Consequently, they suggest that BMB can be omitted in case of unequivocal bone marrow involvement at FDG-PET/CT. Although the results of the study by Chen-Liang et al [1] underline the results of our previous study [2] that FDG-PET has a suboptimal sensitivity for the identification of bone marrow involvement in DLBCL, we cannot agree with their conclusion that bone marrow abnormalities at FDG-PET/CT can confidently designate advanced-stage disease. Increased focal FDG uptake in the marrow is not sufficient evidence to confirm bone marrow involvement.…”
Section: Author Contributionscontrasting
confidence: 69%
“…This concern is reflected by the fact that although bone marrow involvement according to BMB has been established as an important adverse prognostic factor in DLBCL [7], this is not the case for FDG-PET/CT-based bone marrow involvement. Of the five studies that reported the prognostic value of bone marrow involvement at FDG-PET/CT in DLBCL [2,[8][9][10][11], four showed that FDG-PET/CTbased bone marrow status did not have any prognostic value at all [2,[8][9][10]. These observations suggest that false-positive FDG-PET/CT results occur in a considerable proportion of patients with DLBCL and that increased FDG uptake of the marrow is not sufficient evidence to designate advanced-stage disease.…”
Section: Author Contributionsmentioning
confidence: 96%
See 1 more Smart Citation
“…It is a morphologically unique subtype of AML that is classified as AML M3 by the old French-American-British (FAB) system and APL with t(15;17)(q22;q21) by the World Health Organization (WHO) [1]. The resultant PML/RARa fusion protein inhibits differentiation at the promyelocyte stage [7].…”
Section: Discussionmentioning
confidence: 99%
“…Acute promyelocytic leukemia (APL) is a distinct subtype of acute myeloid leukemia (AML) that harbors a unique balanced reciprocal translocation between chromosomes 15 and 17 resulting in the generation of promyelocytic leukemia (PML)-retinoic acid receptor alpha (RARa) fusion gene [1]. Untreated, it runs a fatal course of only weeks, with most succumbing to severe hemorrhagic diathesis.…”
Section: Introductionmentioning
confidence: 99%